Fracture strength of warm mix asphalt concretes modified with crumb rubber subjected to variable temperatures. (14th September 2020) - Pirmohammad, Sadjad; Khanpour, Morteza
Abstract : This paper was aimed to investigate the effects of crumb rubber, weather condition and loading mode on fracture behaviour of warm mix asphalt (WMA) mixtures. For this purpose, two WMA mixtures were prepared such that the first mixture contained Sasobit (called normal WMA concrete) and the second one contained the same Sasobit but was modified by crumb rubber of recycled tyres (called modified WMA concrete). Fracture experiments were performed on semi-circular bend (SCB) specimens made of the normal and modified WMA concretes under different loading modes of I, II and mixed-mode I/II at different weather conditions of CT (constant temperature) and VT (variable temperature). The results demonstrated that the crumb rubber improved the fracture strength of WMA concretes significantly. Furthermore, both the normal and modified WMA concretes at the weather condition of VT resisted against fracture worse than those at the weather condition of CT, signifying that the weather condition of VT adversely affected the fracture resistance of WMA mixtures. It was also found that the WMA concretes were more vulnerable to fracture under mixed-mode I/II than under pure mode I (or II).